The Impact of Opium Dependence and Cigarette Smoking on Human Semen Parameters - Seyed Noureddin Nematollahi-Mahani; Fateme Labibi; Zhinoosossadat Shahidzadeh yazdi; Elahe Karamad; Victoria Habibzadeh; Tayebe Naderi; Aliasghar Ketabchi (Negah Institute for Scientific Communication, 2014)
Introduction: To examine the effects of opium dependence and cigarette smoking on semen quality and sperm parameters, the semen quality of men who abuse opiates and/or smoke cigarettes was investigated in a retrospective study. Methods: Male partners of 1325 infertile couples attending the infertility clinic for intrauterine insemination (IUI) procedure were divided into non-smoking non-opium (NS/NO), smoking and non-opium (S/NO), non-smoking and opium (NS/O), smoking and opium (S/O), and opium dependence regardless of smoking status (O/RS) groups. Two samples were collected from each subject and were analyzed in accordance to WHO criteria. Results: Subjects in different groups were comparable regarding mean age, duration of abstinence, and familial history of infertility, whereas duration of infertility was longer in all groups than in NS/NO group (P<0.05). The volume of semen, liquefaction time and pH differed significantly between S/NO and NS/NO groups (P<0.05). In addition, more men in S/NO group were diagnosed to be teratozoospermic than other groups (P=0.018). Sperm progression was significantly lower in NS/O than in NS/NO group (P<0.05). Conclusion: These findings suggest that opium dependence and cigarette smoking alter semen and sperm production and quality differently.